Transforming Legal Narratives: Postmodernism in South Asian English Literature - Nida Masroor; Mehwish Aslam; Dr Syeda Kaneez Fatima (Journal of Social Science, 2023)
This study examines the relationship between law, literature, and postmodernism within the context of South Asian English literature. The objective of this study is to analyse the historical development of legal narratives and their subsequent influence on notions of human rights, cultural identity, and justice. Examining and challenging legal narratives, "Burnt Shadows" by Kamila Shamsie, "The Kite Runner" by Khaled Hosseini, "The English Patient" by Michael Ondaatje, and "The Sea of Poppies" by Amitav Ghosh use postmodern literary techniques. Using Katherine Belsey's postmodernism paradigm as a theoretical perspective, the purpose of this study is to analyse the deconstructed and reconstructed narratives found in the novels. The primary objective of these academic investigations is to provide a deeper comprehension of the dominant legal discourses in South Asia and their broader implications.